Mbd3/NuRD controls lymphoid cell fate and inhibits tumorigenesis by repressing a B cell transcriptional program - Loughran, S; Comoglio, F; Hamey, F; Giustacchini, A; Errami, Y; Earp, E; Göttgens, B; Jacobsen, S; Mead, A; Hendrich, B; Green, A (Rockefeller University Press, 2017)
Differentiation of lineage-committed cells from multipotent progenitors requires the establishment of accessible chromatin at lineage-specific transcriptional enhancers and promoters, which is mediated by pioneer transcription factors that recruit activating chromatin remodeling complexes. Here we show that the Mbd3/nucleosome remodeling and deacetylation (NuRD) chromatin remodeling complex opposes this transcriptional pioneering during B cell programming of multipotent lymphoid progenitors by restricting chromatin accessibility at B cell enhancers and promoters. Mbd3/NuRD-deficient lymphoid progenitors therefore prematurely activate a B cell transcriptional program and are biased toward overproduction of pro-B cells at the expense of T cell progenitors. The striking reduction in early thymic T cell progenitors results in compensatory hyperproliferation of immature thymocytes and development of T cell lymphoma. Our results reveal that Mbd3/NuRD can regulate multilineage differentiation by constraining the activation of dormant lineage-specific enhancers and promoters. In this way, Mbd3/NuRD protects the multipotency of lymphoid progenitors, preventing B cell-programming transcription factors from prematurely enacting lineage commitment. Mbd3/NuRD therefore controls the fate of lymphoid progenitors, ensuring appropriate production of lineage-committed progeny and suppressing tumor formation.